Sleep Duration and Insomnia in Adolescents Seeking Treatment for Anxiety in Primary Health Care - Haugland, Bente S. M.; Hysing, Mari; Baste, Valborg; Wergeland, Gro Janne; Rapee, Ronald M.; Hoffart, Asle; Haaland, Åshild T.; Bjaastad, Jon Fauskanger (Frontiers in Psychology, 2021)
There is limited knowledge about sleep in adolescents with elevated levels of anxiety treated within primary health care settings, potentially resulting in sleep problems not being sufficiently addressed by primary health care workers. In the current study self-reported anxiety, insomnia, sleep onset latency, sleep duration, and depressive symptoms were assessed in 313 adolescents (12-16 years; mean age 14.0, SD =.84, 84.0% girls) referred to treatment for anxiety within primary health care. Results showed that 38.1% of the adolescents met criteria for insomnia, 34.8% reported short sleep duration (< 7 hours), and 83.1% reported long sleep onset latency (≥ 30 min). Total anxiety symptoms were related to all sleep variables after controlling for age and sex. Furthermore, all anxiety symptom sub-types were associated with insomnia and sleep onset latency, whereas most anxiety subtypes were associated with sleep duration. Adolescents’ depressive symptoms accounted for most of the anxiety-sleep associations, emphasizing the importance of depressive symptoms for sleep. However, anxiety was associated with insomnia and sleep onset latency also among youth with low levels of depressive symptoms. The findings suggests that primary health care workers should assess sleep duration, sleep onset latency, and insomnia in help-seeking adolescents with anxiety.